The Effect of Hydrotherapy on Reducing Blood Sugar Levels in Patients with Diabetes Mellitus - thomas ari wibowo; Setiawan, Agung; Pribadi, Dimas Ria Angga (Jurnal Ilmiah Kesehatan, 2024)
Hydrotherapy is a method of treatment and healing using water. In this case the nurse encourages the patient to increase fluid intake orally and monitor fluid status by consuming water to help the process of removing all toxins in the body, including excess sugar. Purpose: to determine whether there is an effect of hydrotherapy (drinking water) on reducing blood sugar levels in patients with type 2 diabetes mellitus. This research method is literature review to the method of collecting library data. The data is obtained from previous research. The results of research on 10 database-based journal research articles show that there is an effect of hydrotherapy (drinking water) on reducing blood sugar levels in people with diabetes mellitus as many as 9 journals significantly, and only 1 journal has no significant effect but shows a decrease in average blood sugar from before intervention and after intervention. Conclusion: 9 Journals (90%) There is an effect of giving hydrotherapy to decrease blood sugar levels, P-Value is significant < 0.05 and 1 Journal (1%) there is no effect of giving hydrotherapy to decrease in blood sugar levels in patients with diabetes mellitus P Value > 0.05.